Twenty-four years lucerne (Medicago sativa L.) breeder seed production in India: a retrospective study - Chand, Subhash; Roy, Ajoy Kumar; Singh, Tejveer; Agrawal, Rajiv Kumar; Yadav, Vijay Kumar; Kumar, Sanjay; Malaviya, Devendra Ram; Chandra, Amaresh; Yadava, Devendra Kumar (Frontiers in Plant Science, 2023)
Lucerne (Medicago sativa L.) is the second most significant winter leguminous fodder crop after berseem in India. Breeder seed (BS) is the first stage of the seed production chain, as it is the base material for producing foundation and certified seeds. In India, lucerne BS demand has been reduced by 85.58% during the last 24 years (1998–1999 to 2021–2022), declining from 2150 kg to 310 kg. Out of 14 varieties released and notified so far, only nine varieties entered the seed chain since 1998–1999. It shows narrow varietal diversification and, hence, needs robust breeding programs towards enriching genetic variability and varietal development. The present study also highlights the disparity in BS demand and production over the years and puts forth the possible reasons behind the reduction in BS demand and production in the country. Out of the nine varieties, the BS demand of Anand-2 (53.11%) was highest, followed by Type-9 (19.44%) and RL-88 (13.60%). Varietal replacement rate (VRR) was found to be moderate, i.e., 23.67% for the varieties having <5 years old age in the last 3 years (2019–2020 to 2021–2022). It has also been estimated that BS produced (233 kg) during 2021–2022 can cover the approximate area of 6,300 ha at farmers’ fields in 2024–2025 if the seed chain functions 100%, effectively. The present study provides a holistic overview of lucerne BS demand and production, challenges in BS production, and the way forward to develop more varieties and surplus BS production in the country.